2018
DOI: 10.37358/rc.18.1.6088
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Medical Perspective on Novel Dopamine Detection Method

Abstract: Dopamine is very important neurotransmitter and the rapid and effective methods for its determination are of great importance in fundamental medical research. A rapid voltammetric assay for dopamine (DA) detection in presence of ascorbic acid (AA) based on an electrochemically pretreated pencil graphite electrode has been investigated. Differential pulse voltammetry results showed two well-distinguished oxidation peaks for DA and AA at 0.369 V and 0.142 V, respectively, and the method was applied for DA determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…If diagnosed preoperatively by imagistic means it is recommended to perform a diagnostic laparoscopy [12,13]. When a direct hernial sac is identified and it contains an inflamed appendix, a laparoscopic appendicectomy with open mesh repair is recommended, as it reduces the need for an elective appendicectomy later [14].…”
Section: Resultsmentioning
confidence: 99%
“…If diagnosed preoperatively by imagistic means it is recommended to perform a diagnostic laparoscopy [12,13]. When a direct hernial sac is identified and it contains an inflamed appendix, a laparoscopic appendicectomy with open mesh repair is recommended, as it reduces the need for an elective appendicectomy later [14].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the oncological safety margins, our resections involve a 1-2cm distance from the tumor, although research has demonstrated that the rate of recurrence does not seem to be influenced by the resection distance and varies rather according to the size of the tumor. Keeping these aspects in mind, the surgeon must obtain a clear macroscopic resection without lymphadenectomy (26). Although our sample size was small, our group had a postoperative survival rate of 100 % at 1 year.…”
Section: Discussionmentioning
confidence: 95%
“…S2 also delayed the first pain reaction by 58.76% compared to the control group, while S4 delayed by 53.69%. S3 and S5 had negligible analgesic effects (17,18).…”
Section: Experimental Research Regarding Quinazolin-4-ones Derivativementioning
confidence: 93%